Import of agricultural products from Colombia to Czech Republic - Přibylová, Jana (2015)
The demand for tropical fruit in the Czech Republic is rising, it´s a trend in the modern way of life. People in the Czech Republic, and all over the world, demand healthier ways of food consumption. We did research concerning a supply in the supermarkets and consumers. I found out, that a demand for tropical fruit was not very well covered and that people were demanding more variety of tropical fruit and were ready to up pay double prices for it. I compared data about consumption of tropical fruits in Germany, Austria and the Czech Republic. The comparison is drawn from net import of tropical fruit and net import it´s divided per capita. We proved that people in the Czech Republic were consuming fewer kilograms per capita per year than people in Germany and Austria. Annual consumption of tropical fruit in the Czech Republic grew by 7 % during the last five years, while in Germany it amounted to 0,3% and in Austria to 4,5%.